The Influence of Activity Ratio on Liquidity in Manufacturing Companies 2021-2023 - Milala, Yosi Fhina Br; Pane, Aditya Amanda; Sagala, Indah Cahya; Ananda, Rana Fathinah; Dewi, Sucitra (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The aim of this research is to determine the effect of cash turnover, receivable turnover and inventory turnover on liquidity in food and beverage sub-sector manufacturing companies in 2021-2023, partially and simultaneously. The research design used is an associative approach. The population in this study was 47 mining companies listed on the Indonesia Stock Exchange for the 2021-2023 period with a sampling technique based on criteria using purposive sampling, so that the research sample consisted of 31 food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange starting in 2021-2023. In this research, the type of data used is quantitative data. The data source used in this research was obtained from the Indonesia Stock Exchange (BEI) website. The data analysis method uses multiple linear regression analysis with SPSS.25. Based on the results of the t test that has been carried out, it can be concluded that Cash turnover has a positive and significant effect on Liquidity. Receivable turnover has a positive and significant effect on Liquidity. Inventory turnover has a positive and significant effect on Liquidity. Based on the results of the F test, it is concluded that Cash turnover, Receivable turnover and Inventory turnover have a simultaneous influence on Liquidity in Manufacturing Companies in the Food and Beverage Sub Sector 2021-2023